INCREASING OF DIMENSIONALLY-GEOMETRICAL PARAMETERS AND TECHNOLOGICAL CHARACTERISTICS OF INVESTMENT MOLDS IN CASTING UNDER DISPENSABLE PATTERNS - I. G. Sapchenko; S. G. Zhilin; G. M. Savastjanov (Литьë и металлургия, 2009)
The technology of castings gaining in process of investment casting, seeking to reducing of castings costs, enhancement of shell mold properties and gaining castings with improved geometric relationship, which based on application of ceramic shell mold with intermediate porous layer and sump in the form of half of torus, which produced by polymeric model with porosity about 30-40% was developed.